2020
DOI: 10.1086/707664
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting a Landmark Study System: No Evidence for a Punctuated Mode of Evolution inMetrarabdotos

Abstract: Is speciation generally a "special time" in morphological evolution, or are lineage-splitting events just "more of the same" where the end product happens to be two separate lineages? Data on evolutionary dynamics during anagenetic and cladogenetic events among closely related lineages within a clade are rare, but the fossil record of the bryozoan genus Metrarabdotos is considered a textbook example of a clade where speciation causes rapid evolutionary change against a backdrop of morphological stasis within l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 85 publications
2
9
0
Order By: Relevance
“…We captured nuances in the dynamics of trait evolution given changing environmental and ecological conditions over geological timescales and corroborated the lack of phenotypic stasis in the fossil record found in recent work [59]. While previous studies investigate life-history traits [60] and pioneered quantitative genetics using fossil organisms [61,62], this is the first attempt at quantifying trait-fitness associations and understanding how they align with long-term phenotypic evolution, given the backdrop of climate change and ecological interactions.…”
Section: Discussionsupporting
confidence: 79%
“…We captured nuances in the dynamics of trait evolution given changing environmental and ecological conditions over geological timescales and corroborated the lack of phenotypic stasis in the fossil record found in recent work [59]. While previous studies investigate life-history traits [60] and pioneered quantitative genetics using fossil organisms [61,62], this is the first attempt at quantifying trait-fitness associations and understanding how they align with long-term phenotypic evolution, given the backdrop of climate change and ecological interactions.…”
Section: Discussionsupporting
confidence: 79%
“…Genetic diversity levels higher than reported are frequently estimated in taxonomic revisions that include molecular studies, often corroborating distinctions previously suggested based on morphological differences [43,48,51,63]. Intra-specific morphological variation and genetic divergence are not only associated with genetic drift but also with geographical and ecophenotypic factors [59,65]. The observation of the full range of morphological variation in Reteporella and other erect bryozoans is limited by destructive sampling methods [4,6,59].…”
Section: The Genus Reteporella In the Azores Diversitysupporting
confidence: 78%
“…The veracity of these genetic divergence levels was verified by two independent rounds of sequencing for both mitochondrial markers, all resulting in good quality sequences, confirming the genetic distinctiveness of this specimen. Ecological surveys to characterize the habitat at 150 m around Flores and to obtain more samples similar to BRY16 are necessary to clarify whether this constitutes a distinct lineage of R. atlantica or if it is just a product of natural genetic drift in the population [65]. Population genetic studies are needed to clarify the diversity and distribution of R. atlantica in the Azores.…”
Section: The Genus Reteporella In the Azores Diversitymentioning
confidence: 99%
“…Members of the colonial phylum Bryozoa have played a fundamental role in classical debates regarding tempo and mode of morphological evolution (Cheetham, 1986a(Cheetham, , 1986b(Cheetham, , 1987Cheetham et al, 1993Cheetham et al, , 1994Voje et al, 2020), and represent an emerging model system in macroevolutionary, ecological, and paleobiological research (Clark et al, 2010;Di Martino & Liow, 2021Liow et al, 2017;Liow & Taylor, 2019;O'Dea & Jackson, 2009, 2002O'Dea & Okamura, 2000;Okamura et al, 2013). Bryozoans have an old (Cambrian) (Zhang et al, 2021), species-rich (>22,000 described species), and high temporal resolution fossil record (Taylor, 2020).…”
mentioning
confidence: 99%